Efficacy of motavizumab for the prevention of respiratory syncytial virus disease in healthy Native American infants: a phase 3 randomised double-blind placebo-controlled trial. Issue 12 (December 2015) - O'Brien, Katherine L; Chandran, Aruna; Weatherholtz, Robert; Jafri, Hasan S; Griffin, M Pamela; Bellamy, Terramika; Millar, Eugene V; Jensen, Kathryn M; Harris, Brian S; Reid, Raymond; Moulton, Lawrence H; Losonsky, Genevieve A; et al.
Summary: Background: Respiratory syncytial virus (RSV) is a leading cause of acute lower respiratory tract infections in children. We aimed to assess the safety and efficacy of an anti-RSV monoclonal antibody (motavizumab) in healthy term (≥36 weeks' gestational age) infants for the prevention of medically attended RSV acute lower respiratory tract infections. Methods: This phase 3, double-blind, placebo-controlled, randomised trial enrolled healthy Native American infants aged 6 months or younger who were born at 36 weeks' gestational age in southwestern USA, on the Navajo Nation, the White Mountain Apache reservation, and the San Carlos Apache Indian reservation. Participants were randomly assigned (2:1) to receive either five monthly intramuscular doses of motavizumab (15 mg/kg) or placebo. They were followed up for 150 days after the first dose, and the primary endpoints were respiratory admission to hospital with a positive result for RSV by RT-PCR and death caused by RSV. Participants were followed up for medically attended wheezing until they reached age 3 years. Analysis was by intention to treat (ITT). This trial is registered withClinicalTrials.gov, numberNCT00121108 . Findings: During the autumn seasons (October to December) between 2004 and 2007, 2127 infants of the 2596 infants enrolled were randomly assigned to receive either motavizumab (1417) or placebo (710). After ITT analysis, motavizumab resulted in an 87% relative reduction (relative risk [RR] 0·13, 95% CI 0·08–0·21) in the proportion of infants admitted to hospital with RSV (21 [2%] of 1417 participants who received motavizumab; 80 [11%] of 710 participants who received placebo, p<0·0001). Serious adverse events were less common in particpants taking motavizumab (212 [15%]) than particpants on placebo (148 [21%]). Six deaths occurred in study participants (motavizumab, n=4 [0·3%]; placebo, n=2 [0·3%]); none were deemed to be related to the study product. Hypersensitivity events were more common in patients given motavizumab (208 [14·7%]) than in placebo recipients (87 [12·3%]; p=0·14). There was no effect on rates of medically attended wheezing in children aged 1–3 years (190 [14·9%] of participants randomly assigned to receive motavizumab vs 90 [14·0%] participants randomly assigned to receive placebo). Interpretation: To our knowledge, this is the only trial of an anti-RSV antibody to prevent serious RSV disease in healthy term infants. Motavizumab significantly reduced the RSV-associated inpatient and outpatient burden and set a benchmark for the efficacy of RSV prevention strategies. The findings do not support a direct, generalisable, causal association between RSV lower respiratory tract infection and subsequent long-term wheezing in term infants. Funding: MedImmune.